Algunos líquenes interesantes para la Península Ibérica - Fernández-Costas, Daniel; García-Molares, Aida (Botanica Complutensis, 2023)
The presence of 25 species was reported during a survey carried out in the municipality of O Rosal (Pontevedra, NW Spain). Among them, Arthonia anglica and A. ligniaria are new records for the Iberian Peninsula, while Rinodina colobinoides and Usnea erinacea are new records for Spain. In addition, Agonimia opuntiella, Cliostomum griffithii, Coppinsiella ulcerosa, Lecanora barkmaniana, Micarea synotheoides, Physcia vitii, Reichlingia zwackhii, Rinodina biloculata, R. excrecens, R. conradii and R. pyrina are recorded for the first time in Galicia. Another 10 species included in this publication are new records for the province of Pontevedra.